OWNERSHIP IN ISLAMIC AND ECONOMIC CONCEPTS RELATIONSHIP TO SCARCITY PROBLEMS - Rodi Syafrizal; M. Yasir Nasution; Sugianto (PT. Radja Intercontinental Publishing, 2024)
The problem of scarcity and limited resources (scarcity) is what is currently becoming a problem. The relationship between the concept of ownership in Islamic economics and the scarcity phenomenon in Indonesia involves various aspects, including individual ownership rights, social responsibility, and the application of sharia principles. This research aims to examine the relationship between the concept of ownership in Islamic economics and the problem of scarcity which occurs due to the unequal distribution of natural and individual wealth. This research use desciptive qualitative approach. The results of this research show that essentially everything in nature belongs to Allah SWT, humans are only recipients of a deposit to manage and empower existing treasures or resources. The concept of ownership in Islamic economics emphasizes social responsibility and wise management of natural resources. Applying these principles can help prevent overexploitation and harm to the environment. In resource empowerment, Islamic ownership emphasizes the redistribution of wealth to overcome the problem of social equality gaps.